Outcomes of the novolimus-eluting bioresorbable vascular scaffold in real world clinical practice - Çakal, Beytullah; Çakal, Sinem Deniz; Karaca, O?uz; Omaygenç, Mehmet Onur; Kızılırmak, Filiz; Güneş, Hacı Murat; Özcan, Özgür Ulaş; İbişoğlu, Ersin; Boztosun, Bilal (Edizioni Minerva Medica, 2021)
BACKGROUND: Most of the current data regarding the use of bioresorbable scaffolds (BRS) come from everolimus-eluting stent platforms. Adverse events with the everolimus-eluting BRSs which are the most comprehensively characterized BRS, hampered the clinical use of other BRS. There is paucity of published data regarding long term use of novolimus-eluting BRS.METHODS: This study sought to evaluate the performance of novolimus-eluting BRS device at midterm follow-up in real world clinical practice. One hundred and forty four patients (mean age 57.5 ± 9.7 years, 78.5% male) treated with 206 scaffolds between October 2015 and December 2017 were enrolled. A device-oriented composite endpoint (DOCE) comprising cardiac death, target vessel myocardial infarction (TV-MI), clinically driven target lesion revascularization (TLR) and rate of scaffold thrombosis were investigated.RESULTS: During a mean follow-up of 33±9 months, DOCE occured in 9 patients (6.3%) of which cardiac death occured in 2 patients (1.4%), and clinically-driven TLR in 7 patients (4.9%), TV-MI in one patient. Target vessel revascularization (TVR) was observed in nine patients. None of the patients experienced scaffold thrombosis.CONCLUSIONS: The use of novolimus-eluting BRS in this real world population achieved good clinical outcomes.
Keywords: Bioresorbable Vascular Scaffold; Percutaneous Coronary Intervention; Major Cardiac Events